Envelope transient simulation of nonlinear electronic circuits using multi-rate Runge-Kutta algorithms - Oliveira, Jorge dos Santos Freitas de (2011)
Time-step integration is a popular technique commonly used for the envelope transient simulation of an electronic circuit. However, many kinds of circuits are characterized by widely separated time scales, which lead to significant computational costs when numerically solving its differential systems. Even so, this situation can be exploited in an efficient way using multi-rate methods, which integrate system components with different step sizes. In this paper two multi-rate Runge-Kutta schemes are studied and tested in terms of computational speed and numerical stability. The results for linear stability analysis here obtained are much more coherent with the characteristics of the methods than the ones previously presented in [6].